ВЛИЯНИЕ ТИРЕОИДНОЙ ДИСФУНКЦИИ НА ПСИХОЭМОЦИОНАЛЬНЫЙ СТАСУС ПАЦИЕНТОВ - Курбанов Дониёр Бахтиёрович; Хажидедаева Назокатхон Али кизи; Абдуллаева Зебохон Хамидулло кизи; Жамолиддинов Нурмухаммад Жалолиддин оглы (TADQIQOTLAR, 2025)
Abstract. This review examines psychoemotional disorders associated with thyrotoxicosis and hypothyroidism, including anxiety, depression, and cognitive impairments. It is noted that thyroid dysfunction has a significant impact on the central nervous system and may mask the somatic nature of the disease. Special attention is given to obsessive-phobic symptoms, asthenic conditions, hypothyroid encephalopathy, and evening variability in psychoemotional states. The aim of the review is to summarize and analyze current scientific data on the relationship between thyroid dysfunction and psychoemotional disorders in order to raise awareness among physicians of various specialties about the importance of a comprehensive, interdisciplinary approach to diagnosing and treating such patients. The literature used is primarily based on authoritative clinical guidelines, textbooks, and contemporary scientific publications.